Model Kepemimpinan Situasional Pada Perusahaan Keluarga ( Kasus UKM di Sentra Industri Wedoro Sidoarjo ) - Wahjono, Sentot Imam (BISMA (Bisnis dan Manajemen), 2018)
Small and Medium Enterprises (SMEs) in general, grow and develop from the bottom armed with the spirit of entrepreneurship.After survived and developed into a company, usually a family company that is driven by human resources that have a family linkage to each other. As a family company that emphasizes harmony, need a central figure as a leader capable of moving the company effectively. The effectiveness of leadership in family firms in the model of situational leadership is largely determined by the adjustment of the maturity of the employees with the leadership style practiced. In the event of compliance hence could be expected would be easy to achieve corporate objectives include achieving sustained earnings growth that is sustainable. One indicator of leadership effectiveness is the satisfaction and performance improvement. Indicated satisfaction with the feeling satisfied and happy under certain circumstances surrounding the employees' daily work, including: how leaders deal with employees, provide fringe benefits, providing a space of expression, and others. This research examines the relationship between leadership effectiveness with satisfaction. Leadership model using the situational leadership theory of Hersey-Blanchard. The results turned out to support the theory that there is a positive and significant relationship between leadership effectiveness and job satisfaction.